Eine Höhle für Platon. - Raschke-Stuwe, Ingrid; Murauer, Waltraud; Valavuo, Niina; Villa Ingenohl, Bonn (Bonn : Montag Stiftung Bildende Kunst, 2009)
Albrecht, Jürgen ; Fuchs, Harald ; Gliese, Carsten ; Kaufmann, Andreas M. ; Kuball, Mischa ; Kutscher, Vollrad ; Sudhues, Max
Published on the occasion of the art project 'A Cave for Plato', which took place in the Villa Ingenohl, Bonn, from 26 April to 28 June, 2009
kunstcatalogus